O trabalho do (a) assistentes social na atenção básica à saúde em UBS's : a gravidez na adolescência em Parintins - AM - Picanço, Dayana Feitosa (Brasil, 2023)
Bearing in mind that the subject will help to know the main causes that lead teenagers to become pregnant and their main consequences, which are a cause for concern as well as for the community, as it is a public health issue and a social problem. The analysis and reflection on the subject will be able to contribute for a future elaboration of strategies for the resolution of the problem, it is researched on the work of the (ª) social assistant in the basic attention to the health in UBS´s: The pregnancy in the adolescence in Parintins – AM, in order to analyze the work of the Social Worker in coping with early pregnancy in UBSs in Parintins - AM. Therefore, it is necessary to know about the debate on early pregnancy in Parintins - AM, to describe the attributions and competences of the Social Worker in dealing with early pregnancy in UBSs in Parintins - AM; and Mapping actions and strategies of Social Workers regarding guidance and monitoring of pregnant teenagers in Parintins-AM. A field research was then carried out in the municipality of Parintins-AM, in basic health care in 2 (two) Basic Health Units (UBS), namely UBS Tia Léo and UBS Waldir Viana . The field research was carried out between October and December 2022, with 2 (two) Social Workers working in both basic health units. This leads to the conclusion that the professional Social Worker has a very important role in the care of adolescent mothers, and in the health and assistance services related to this public, since it contributes to the well-being of adolescents during this cycle, ensuring the right to social protection when accessing social services.